2017
DOI: 10.1159/000454891
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Lesions through Deep Brain Stimulation Electrodes in Movement Disorders: Case Report and Review of the Literature

Abstract: Background: Although there are few reports of radiofrequency lesions performed through deep brain stimulation (DBS) electrodes in patients with movement disorders, experience with this method is scarce. Methods: We present 2 patients who had been previously treated with DBS of subthalamic nuclei (STN) and the ventral intermediate (VIM) nucleus of the thalamus for Parkinson's disease and essential tremor, respectively, and underwent a radiofrequency lesion through their DBS electrodes after developing a hardwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Thus, radiofrequency lesioning is only applied unilaterally and allows the creation of small and localized lesions. Its effectiveness and low cost made this procedure suitable for the surgical treatment of tremors in the past [120][121][122] but due to the high incidence of side effects, it has almost been abandoned…”
Section: Radiofrequency Lesioning Of the Vimmentioning
confidence: 99%
“…Thus, radiofrequency lesioning is only applied unilaterally and allows the creation of small and localized lesions. Its effectiveness and low cost made this procedure suitable for the surgical treatment of tremors in the past [120][121][122] but due to the high incidence of side effects, it has almost been abandoned…”
Section: Radiofrequency Lesioning Of the Vimmentioning
confidence: 99%
“…Also, RF ablations are favored in many neurosurgical units because of their relative straightforwardness, short duration of surgery, persistent effect, and low rate of complications [ 27 , 28 ]. Furthermore, RF lesioning was successfully applied after ineffective DBS treatment [ 29 ] and even through DBS electrodes [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, other reports showed that thalamotomy may be considered as an option for treating patients who fail to respond to DBS or suffer from adverse effects of stimulation. In some cases, RF lesioning was successfully applied through DBS electrodes [ 19 , 20 ]. Meanwhile, ablative interventions are relatively easier, have a shorter duration, patients do not need regular visits to doctors after treatment, and never lead to DBS withdrawal syndrome, which could develop after the sudden depletion of the implantable generator.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a square biphasic pulse delivered through DBS electrodes demonstrated significant improvement in postural tremor, tremor at rest, and action tremor when compared to conventional DBS settings as well as sustained tremor improvement [40,41]. Another interesting application involves administering radiofrequency through previously implanted DBS electrodes, with the aim to provide precise ablation localization and success in ET reduction in a limited set of cases [42][43][44].…”
Section: Nuanced Surgical Methodsmentioning
confidence: 99%